2020
DOI: 10.1108/bfj-11-2019-0868
|View full text |Cite
|
Sign up to set email alerts
|

Persuasiveness of organic agricultural products

Abstract: PurposeThe study discusses organic agricultural product persuasion using an empirical survey. This study argued that strong argument persuasive advertising message would trigger individuals' self-reference to the harm of pesticide residue in non-organic agricultural product, which would raise their purchase intention of organic agricultural product.Design/methodology/approachThe present study conducted an empirical investigation in Taiwan by recruiting 527 Taiwanese participants using the convenience sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…Notably, our study is possibly among the first to examine the moderating effect of perceived effectiveness on the links organic food consumption → perceived health risk and organic food consumption → health attitude. The Chou et al (2020) and Liang and Lim (2021) studies might be of relevance herein as they showed that consumers with perceived health risk do not consume harmful food products such as inorganic food. As a result, consumers' self‐efficacy may actually assist them in avoiding such products, and instead consume organic foods in order to remain healthy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Notably, our study is possibly among the first to examine the moderating effect of perceived effectiveness on the links organic food consumption → perceived health risk and organic food consumption → health attitude. The Chou et al (2020) and Liang and Lim (2021) studies might be of relevance herein as they showed that consumers with perceived health risk do not consume harmful food products such as inorganic food. As a result, consumers' self‐efficacy may actually assist them in avoiding such products, and instead consume organic foods in order to remain healthy.…”
Section: Discussionmentioning
confidence: 97%
“…A possible explanation could be that consumers' perception of health risks effectively motivates them to avoid eating unhealthy foods such as fast foods and fertilizer-grown foods. For example, we noted that consumers were reluctant to consume inorganic (not healthy) food during the peak of the first and second waves of the COVID-19 pandemic, fearing that it might reduce their immunity levels and make them more susceptible to getting infected (Chou et al, 2020). Therefore, it could be affirmed that consumers who Our results also support H1c (β = 0.537; P < 0.001), which held that perceived health risk is positively and significantly correlated with health attitude.…”
Section: Discussionmentioning
confidence: 99%
“…(Michaelidou and Hassan, 2008;Mai and Hoffmann, 2012;Shin and Mattila, 2019). Chou et al (2020) proposed that individuals who are health conscious perceive fear of a high level of risk associated with the consumption of nonorganic products, which increases an individual's purchase intention of organic products.…”
Section: Moderating Role Of Health Consciousnessmentioning
confidence: 99%
“…Petty et al (1986) maintain that when consumers actively process information with a strong argument, they are generally biased toward generating favourable ideas. Consequently, when consumers process messages with a weak argument, they will eventually generate irrational ideas (Chou, Wang, Lai, Tung, Yang & Tsai, 2020). When consumers rationally interpret argument with the focus on the key message (strong argument), they tend to make judgement on the basis of the argument displayed in the message (Chou, Wang, Lai, Tung, Yang & Tsai, 2020).…”
Section: Theoretical Reviewmentioning
confidence: 99%